Backstepping Control of Photovoltaic-Grid Hybrid Power Feed Water Pump. Issue 1 (July 2017) - El Fadili, A.; Cuny, F.; El Magri, A.; Stitou, M.; Giri, F.; Janik, J.M.; Chaoui, F.Z.
Abstract: We are considering the problem a controlling of photovoltaic-grid pumping system. The system consists of a PV panel, a PWM AC/DC rectifier connected to a single-phase grid, an association of a PWM DC/AC inverter - squirrel cage induction motor, and a centrifugal water pump. The control objectives are fourfold: (i) forcing the pump water flow rate to track any reference signal (ii) regulating the rotor flux norm to its nominal value (iii) regulating the DC Link voltage to a reference value to meet the maximum power point tracking (MPPT), (iv) and the power factor correction (PFC). To meet these control objectives, we first develop a nonlinear model of the whole controlled system in the Park-coordinates. Then, a multi-loop nonlinear controller is synthesized using the backstepping design technique. In addition to closed-loop global asymptotic stability, it is proved that all control objectives (water flow rate tracking, rotor flux regulation, DC link voltage regulation and unitary power factor) are asymptotically achieved.